Case Analysis of Islamic Religious Education (PAI) Learning: Members' Active Participation in Congregational Prayers at the 1705/Nabire Military District Command - Alim Bakhri; Dika Tripitasari (International Journal on Advanced Science, Education, and Religion, 2026)
This study aims to analyze Islamic Religious Education (PAI) learning related to member activeness in congregational prayer at the 1705/Nabire Military District Command (Kodim). The focus of the study is the factors influencing member participation and coaching strategies to increase the consistency of collective worship. The main problem is the lack of consistency among some members due to busy official duties, operational dynamics, and an unstructured reinforcement system, resulting in a gap between understanding of PAI values ​​and daily practice. A qualitative approach with a case study method was used to obtain an in-depth overview. Data were collected through observation, interviews, and documentation, analyzed descriptively and interpretively using behaviorist learning theory that emphasizes the stimulus-response relationship and the importance of reinforcement. Religious behavior such as congregational prayer can be formed through consistent stimuli, positive reinforcement, and structured habituation. The results show that positive reinforcement in the form of appreciation, recognition, and moral support from leaders increases member motivation. Clear scheduling, consistent supervision, and leadership role models also build a religious culture. The integration of PAI values ​​with the culture of military discipline supports behaviorist habituation. However, strengthening intrinsic motivation is still necessary so that worship grows from internal awareness, not solely from rules or rewards. The behaviorist approach is relevant, but its effectiveness is optimal if combined with comprehensive religious character development.